2021
DOI: 10.1344/der.2021.40.122-140
|View full text |Cite
|
Sign up to set email alerts
|

Digital Competences for Smart Learning During COVID-19 in Higher Education Students from Spain and Latin America

Abstract: Networked society has become the context of a technology-supported environment for learning and teaching. The access to knowledge is essentially mediated through connected smart devices that nurture digital skills and define a new learning concept: Smart learning, moreover during COVID-19 pandemic. This study aims to present a descriptive and correlational analysis focusing on the development of smart learning in three different areas when using the Internet: use, learning and critical thinking from the perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…The fact that basic computer skills had lower value differs from what was found in other studies, such as those of Núñez-Canal and Escoda, because the studies were carried out in Europe, where the use of computer platforms has been used since before the pandemic began, being a skill developed since the school stage. It should be borne in mind that digital competencies are necessary for lifelong learning in the near future, conditioned by the global situation of the pandemic experienced (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that basic computer skills had lower value differs from what was found in other studies, such as those of Núñez-Canal and Escoda, because the studies were carried out in Europe, where the use of computer platforms has been used since before the pandemic began, being a skill developed since the school stage. It should be borne in mind that digital competencies are necessary for lifelong learning in the near future, conditioned by the global situation of the pandemic experienced (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The study's objective was to measure the level of academic anxiety in students and identify the variables associated with it that affect the perception of the Institutional management assessment led by higher education institutions in Ibero-America, since March 2020, because of the pandemic of COVID-19. The correlational study was de-signed under a non-experimental quantitative methodology, following different studies launched during the pandemic, like those carried out by Pérez Escoda, Lena-Acebo, and García-Ruiz (2021), andCoronado, Rockcastle, andKwok (2021), for example. The objective is also related to the hypothesis mentioned in this study: H1= The anxiety levels observed in the students were due to external and internal variables associated with the academic management faced by higher education institutions because of the pandemic scenario experienced in March 2020; H2= Higher institutions require an organizational culture based on the provision of soft skills and support measures that have allowed students to confront the pandemic scenario since March 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of a modern and digital learning environment in which many digital tools and advanced technology are available. Specific principles should be adopted to ensure the success of this learning, as the study of Perez et al (2021) confirmed one of these principles, which is the use of modern approaches to achieve the desired learning objectives. Therefore, in learning environments, several types of interactions are implemented, including student interaction with the materials, student interaction with the teacher, and student interaction with the student (Wang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%